(untitled) (The Conference Hub, 2025)
Biblionymic components in phraseological units represent references to sacred, literary, or historical texts. This article explores proverbial phraseological units containing biblionymic elements in Uzbek and English. The study focuses on semantic, structural, and cultural aspects of such units. The analysis reveals that English phraseology is strongly influenced by Biblical sources, while Uzbek phraseology reflects a combination of religious, literary, and folkloric traditions. The research demonstrates how biblionymic phraseology serves as a cultural memory of societies.